Convenient synthesis of alpha,alpha `- homo- and alpha,alpha `-hetero-bifunctionalized poly(epsilon-caprolactone)s by ring opening polymerization: the potentially valuable precursors for miktoarm star copolymers - Patil, Sachin S.; Tawade, Bhausaheb V.; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2016)
Two new ring opening polymerization (ROP) initiators, namely, (3-allyl-2-(allyloxy)phenyl)methanol and (3-allyl-2-(prop-2-yn-1-yloxy)phenyl)methanol each containing two reactive functionalities viz. allyl, allyloxy and allyl, propargyloxy, respectively, were synthesized from 3-allylsalicyaldehyde as a starting material. Well defined -allyl, -allyloxy and -allyl, -propargyloxy bifunctionalized poly(epsilon-caprolactone)s with molecular weights in the range 4200-9500 and 3600-10,900 g/mol and molecular weight distributions in the range 1.16-1.18 and 1.15-1.16, respectively, were synthesized by ROP of epsilon-caprolactone employing these initiators. The presence of -allyl, -allyloxy and -allyl, -propargyloxy functionalities on poly(epsilon-caprolactone)s was confirmed by FT-IR, H-1, C-13 NMR spectroscopy, and MALDI-TOF analysis. The kinetic study of ROP of epsilon-caprolactone with both the initiators revealed the pseudo first order kinetics with respect to epsilon-caprolactone consumption and controlled behavior of polymerization reactions. The usefulness of -allyl, -allyloxy functionalities on poly(epsilon-caprolactone) was demonstrated by performing the thiol-ene reaction with poly(ethylene glycol) thiol to obtain (mPEG)(2)-PCL miktoarm star copolymer. -Allyl, -propargyloxy functionalities on poly(epsilon-caprolactone) were utilized in orthogonal reactions i.e copper catalyzed alkyne-azide click (CuAAC) with azido functionalized poly(N-isopropylacrylamide) followed by thiol-ene reaction with poly(ethylene glycol) thiol to synthesize PCL-PNIPAAm-mPEG miktoarm star terpolymer. The preliminary characterization of A(2)B and ABC miktoarm star copolymers was carried out by H-1 NMR spectroscopy and gel permeation chromatography (GPC). (c) 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2016, 54, 844-860
Keywords: 3-allylsalicyaldehyde; alpha `-allyloxy and alpha-allyl; alpha `-propargyloxy bifunctionalized poly (epsilon-caprolactone)s; alpha-allyl; atom transfer radical polymerization; orthogonal reactions; ring-opening polymerization; star copolymers